THE EFFECT OF OUTDOOR LEARNING ON STUDENTS’ STORYTELLING ABILITY - R.Andi Ahmad Gunadi; Maesaroh Lubis (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2021)
Abstract:Learning outside the classroom is carried out by teachers to improve students’ competences in a particular subject. In this study, learning outside the classroom is conducted to complete the assignment of Indonesian subjects with the topic